Tourism Consumer Behaviour and Destination Awareness in Cross-Border Leisure Travel - Harjula, Minna (My University, 2025)
This study used a survey to explore and analyse the characteristics of Estonian tourism behaviour when planning to travel to a cross-border destination, Linnanmäki in Helsinki. Tourism behaviour is a multidimensional entity that is influenced by both external and internal factors. Therefore, this study delved into the effects of both aforementioned factors by examining internal travel motivations, the destination image of Linnanmäki, and the target group’s social media behaviour. The study was conducted as an exploratory study, as the aim was to delve into the phenomenon without separate hypotheses in order to gain a broad understanding of the topic. The sampling method was self-selected sampling, in which the individuals themselves choose to participate in the sample. The survey was distributed in various Estonian Facebook groups and through the Linnanmäki Estonian newsletter. 121 Estonians responded to the survey. The survey used a 5-point Likert scale, where 1 means “completely disagree” and 5 means “completely agree”. Before the actual distribution of the survey, a back translation process was carried out, which ensured that the Estonian-language survey fully corresponds to the original English-language survey. The collected data was analysed quantitatively using SPSS and jamovi. SPSS was used in particular for descriptive analyses and reliability analysis. Confirmatory factor analysis (CFA) and a multiple linear regression analysis were implemented using jamovi. The results of the study show that Estonian travel intention to Linnanmäki amusement park is explained in particular by the preference for interaction and the cognitive properties of the destination image. In addition, the results show that Linnanmäki is very well known in Estonia, and that an increasing number of Estonians associate Linnanmäki with their intention to travel to Finland. From the perspective of marketing adaptation, the results show that Finland and Estonia are culturally very close to each other, which is why there is no great need for destination marketing adaptation. According to the results of the study, Estonians prefer to search for information about international travel destinations in their native language, which confirms the need to maintain Linnanmäki's Estonian-language communication channels.

Tässä tutkielmassa selvitettiin ja analysoitiin kyselytutkimuksen menetelmin virolaisten turismikäyttäytymisen piirteitä aikomuksenaan matkustaa Viron rajat ylittävään kohteeseen, Helsinkiin Linnanmäelle. Turismikäyttäytyminen on moniulotteinen kokonaisuus, johon vaikuttavat sekä ulkoiset että sisäiset tekijät. Tässä tutkielmassa syvennyttiin molempien edellä mainittujen vaikutuksiin tutkimalla sisäisiä matkustusmotivaatioita, mielikuvaa Linnanmäestä matkakohteena ja kohderyhmän sosiaalisen median käyttäytymistä. Tutkielma on toteutettu eksploratiivisena, sillä ilmiöön haluttiin syventyä ilman erillisiä hypoteeseja saavuttaakseen laajan käsityksen aiheesta. Otantamenetelmänä toimi itsevalikoituva otanta, jossa yksilöt itse valitsevat osallistumisensa otokseen. Kyselyä jaettiin erilaisissa virolaisissa Facebook-ryhmissä sekä Linnanmäen Viron uutiskirjeen kautta. Kyselyyn vastasi 121 virolaista. Kyselyssä hyödynnettiin Likert-skaalaa asteikolla 1–5, jossa arvo 1 tarkoittaa “täysin eri mieltä” ja arvo 5 “täysin samaa mieltä”. Ennen kyselyn varsinaista jakelua toteutettiin back translation -prosessi, jonka myötä varmistuttiin, että vironkielinen kysely vastaa täysin alkuperäistä englanninkielistä kyselyä. Kerätty data analysoitiin kvantitatiivisesti SPSS-ohjelmalla sekä jamovi-ohjelmalla. SPSS-ohjelmaa käytettiin erityisesti deskriptiivisiin analyyseihin sekä reliabiliteettianalyysiin. Konfirmatorinen faktorianalyysi (CFA) sekä usean selittäjän lineaarinen regressiomalli toteutettiin jamovi-ohjelmalla. Tutkielman tulokset osoittavat, että virolaisten matkustusaikomusta Linnanmäen huvipuistoon selittävät erityisesti mieltymys vuorovaikutukselle ja kohdemielikuvan kognitiiviset ominaisuudet. Lisäksi tulokset osoittavat, että Linnanmäen tunnettuus Virossa on erittäin vahva, ja yhä useampi virolainen assosioikin Linnanmäen aikomukseensa matkustaa Suomeen. Markkinoinnin adaptoinnin näkökulmasta tulokset taas osoittavat Suomen ja Viron olevaan kulttuurisesti hyvin lähellä toisiaan, minkä johdosta suurta tarvetta kohdemarkkinoinnin adaptoinnille ei ole. Tutkielman tulosten mukaan virolaiset etsivät tietoa kansainvälisistä matkakohteista mieluiten äidinkielellään, mikä vahvistaa tarvetta ylläpitää Linnanmäen vironkielisiä viestintäkanavia.
Keywords: fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business